Investigation of single wall carbon nanotubes electrical properties and normal mode analysis: Dielectric effects - V. S. Lee (2018)
Besides thermodynamic information, vibration can identify modes of a molecule by comparison of the spectroscopy and parameterize force field. By the application of group theory with the state of projection operators, a systematic method for getting the vibrational model of molecules such as the (3, 0), (4, 0), (5, 0) nanotubes was proposed. The U matrix from the combination of primitive's harmonic vibrations was calculated and the effect of dielectric constants on the mechanism of these vibrations in nanotubes was studied. We found that in the high dielectrics the frequency of vibration has alternative behavior, however by the decreasing of the dielectrics, this behavior change to stable situation of geometry. The calculated data shown in Tables and Figures are in correspondence with some behavior of nanotubes. © 2009 Pleiades Publishing, Ltd.